Controle térmico de alta exatidão e sua aplicação na determinação de propriedades térmicas de materiais - Nascimento, Leonaldo José Lyra do (2012)
This paper presents a theoretical and experimental study of a PID control-Proportional, Integral and Derivative using PELTIER module that achieves precision of about 0.01oC. It is developed to study the integrated instrumentation and control heat transfer. Based on this we developed a heat signal generator on a flat surface and applied to the measurement of thermal properties, in a system similar to electrical circuit. After several experiments, the results indicates the validity of the proposal.